Observations of reservoir quality alteration in proximity to igneous intrusions for two distinct sandstones in Scotland. (July 2021) - Duffy, Marcus; Farrell, Natalie; Raeside, Ronan; Muirhead, David; Healy, David; Brasier, Alex; Schofield, Nick
Abstract: Igneous intrusions are common features within rifted sedimentary basins. With advances in technology, exploration has progressed into more complicated petroleum systems where sediments are segmented and altered by networks of dykes and sills. Magmatism increases temperatures and fluid pressures within adjacent sedimentary host rocks. This can lead to mobilisation of mineral-rich hot fluids through pores and fractures, which alters the host rock microstructure via both mineralisation and dissolution. However, few studies have quantified the impact of intrusions on reservoir quality, specifically on host rock pore networks and their ability to conduct fluid. This study uses a combination of plug porosity and permeability, optical, SEM and cathodoluminescence microscopy and XRD to investigate the mineralogical and reservoir quality changes to sandstones within thermal aureoles. In contrast to published models, associating igneous bodies with reduction of reservoir quality in the host rock, our analyses of two intruded sandstones show that alteration and mobilisation of pore filling minerals and clays can also result in enhancement of porosity and permeability at the intrusion-host rock contact. This study identifies the microstructural and chemical changes which produce these reservoir characteristics and discusses the implications of these processes on reservoir quality and fluid migration in intrusion-rich sedimentary basins. Highlights: Field and laboratory analyses of sedimentary host rock samples from within intrusion aureoles. Reservoir properties shown to be both negatively and positively affected. Highly porous zone could be very useful to migration of fluids post-intrusion. Thermal and hydrothermal alteration can have significant impacts on host rock properties.